A novel energy efficient SFCL with a silver-free contact switchgear for application in electricity and transportation. - Mamalis, A.G.
A novel concept of a switchgear based on the combination of an AC superconducting fault current limiter (SFCL) and silver-free electrical contacts is proposed. In the combined system SFCL+switchgear, it is possible to employ cheaper materials for electrical contacts. The SFCL device includes inductive coupling of high-Tc superconducting active elements, in the form of layered flat rings of a Bi1.8Pb0.3Sr1.9Ca2Cu3Ox compound, prepared by a solid-state reaction technique. Experimental results obtained by testing a prototype SFCL in short circuit regime at AC 50 Hz under quasistationary conditions are presented. The use of the superconducting rings enables a wide range variation of the dissipated power. Copper/diamond composites, prepared by explosive synthesis, are employed as contact materials for the switchgear. The addition of particles (<1 μm) leads to improved mechanical characteristics and increased stability of the composite materials. The combination of switchgear with silver-free electrical contacts and SFCL allows a short circuit regime to withstand the switchgear and provides increased system reliability.
Keywords: 50 Hz; AC superconducting fault current limiter; BiPbSrCaCuO; HTSC active elements; Contact materials; Copper/diamond composites; Energy efficient limiter; Explosive synthesis; Hollow cylinder; Increased stability; Inductive coupling; Layered flat rings; Quasistationary conditions; Short circuit regime; Silver-free contact switchgear; Solid-state reaction technique; System reliability; Wide dissipated power variation